Interdisciplinary teaching in law: study on Indonesian law schools - PRIHANDONO, I.; YUNIARTI, D.S. (Utopía y Praxis Latinoamericana, 2020)
ABSTRACT The study by legal scholars and educators argue that an interdisciplinary approach in teaching law is inevitable. This article seeks to analyze two questions: being first, to what extent law schools in Indonesia adopt interdisciplinary subjects into the curriculum. Second, to what extent these interdisciplinary subjects are relevant to the government’s Industry 4.0 Roadmap. This study analyses the curriculum of law schools, both in private and public universities across Indonesia, as well as making the comparison with other universities in ASEAN. These samples of law schools represent three major regions of Indonesian archipelagos; these are the eastern, central and western region. RESUMEN El estudio realizado por especialistas en derecho y educadores argumenta que el enfoque interdisciplinario en la enseñanza del derecho es inevitable. Este artículo busca analizar dos preguntas: en primer lugar, en qué medida las facultades de derecho en Indonesia adoptan materias interdisciplinarias en el plan de estudios. Segundo, hasta qué punto estos temas interdisciplinarios son relevantes con la Hoja de ruta de la Industria 4.0 del gobierno. Este estudio analiza el plan de estudios de las facultades de derecho, tanto en universidades privadas como públicas de toda Indonesia, y también compara con otras universidades de la ASEAN. Estas muestras de facultades de derecho representan tres regiones principales del archipiélago de Indonesia, estas son: la región oriental, central y occidental.